The analysis of unfixed balance in thermal exchange/Nestacionarių šilumos mainų pastatuose balanso analizė - Juodvalkis, Jonas; Blaževičius, Egidijus; Vipartas, Ramūnas Albertas (Journal of Civil Engineering and Management, 2000)
Today the tendency of building renovation is one-sided, ie thermal resistivity of enclosure constructions is being increased ignoring the temperature control possibilities in flats. Appreciable heat savings may be achieved solely through a duly coordination of the constructive building solutions with the type and power of heating systems and by the evaluation of an unfixed character of heat exchange. In the proposed method a building is treated as a heterogeneous body (∞>Bi>0). The conditions of the 3rd rate are accepted for the heat exchange between the elements of this body and the surroundings (1). The result of the equation solution is the determination of temperature alteration law in each element of a heterogeneous body (2). The non-monolithic enclosure constructions having a final number of elements may be changed by an equivalent monolithic body with equivalent thermal properties (3; 4). The following factors in the unfixed heat exchange balance system of equations have been taken into consideration: – the power of a heat source, its thermal capacity, the intensivity of heat delivery; – the receptivity of interior constructions of a building (its equipment and partitions) and of inner air, the intensity of heat exchange;– thermal resistivity of exterior enclosures of a building, heat receptivity, the intensity of heat exchange with the outside air. The solutions of this equation system gives the following parameters:– the optimal thermal comfort for a particular building; – the most suitable heating system from the point of view of energy; – control possibilities of the inner temperature in a building; – the optimal power of a heat source and the effect of the energy expenditure caused by the heating of a building; – working conditions of a heating source; – the rate of outside temperature fluctuation under control of the working conditions of a heating source; – the effect of different materials on the working conditions of a building and on energy expenditure in building constructions; – the effect on building energetic characteristics of the order of layer distribution in exterior enclosures as well as the intensivity of heat delivery in the environment (wind effect).First Published Online: 26 Jul 2012